Isoelectric focusing followed by affinity immunoblotting to detect monoclonal free light chains in monoclonal gammopathies: Comparison with immunofixation electrophoresis and free light chain ratio - Zeman, David; Štork, Martin; Švancarová, Lenka; Borský, Marek; Pospíšilová, Michaela; Adam, Zdeněk; Beňovská, Miroslava; Pour, Luděk (Annals of clinical biochemistry, 2024)
BACKGROUND: Isoelectric focusing (IEF) is a method with an exquisite resolution, and coupled with affinity immunoblotting (AIB), it can provide superior sensitivity to detect monoclonal free light chains (FLC). METHODS: We tested the hypothesis that IEF/AIB is more sensitive and specific for monoclonal FLC detection in serum and urine samples than conventional methods, that is, electrophoresis (ELP), immunofixation (IF) and serum FLC ratio assessment. Investigation included 107 samples of 68 patients, among which 21 multiple myeloma patients were recently tested for minimal residual disease and 18 patients with AL amyloidosis. RESULTS: Monoclonal FLC were detected by IEF/AIB in 37% of serum samples negative for monoclonal FLC on ELP/IF. As for urine samples, significant advantage of the IEF/AIB over ELP/IF was not demonstrated. Considering both serum and urine results, IEF/AIB definitely revealed monoclonal FLC in 20/83 (24%) of ELP/IF-negative samples. FLC ratio was abnormally high (>1.65) in all 11 patients definitely positive for monoclonal FLC kappa by IEF/AIB but also in 16/47 (34%) IEF/AIB-negative samples. Abnormally low values (<0.26) were found only in 10/28 samples (36%) positive for monoclonal FLC lambda. Appropriate use of renal FLC ratio reference range reduced the number of presumably false positives (6/47, i.e. 13%) but not false negatives (17/28, i.e. 61%). CONCLUSIONS: The IEF/AIB method is more sensitive than IF and might be used in patients with negative IF results before deciding whether to proceed to minimal residual disease testing.
Keywords: imunoblotting; Sensitivity and Specificity; senzitivita a specificita; lehké řetězce imunoglobulinů; Humans; Immunoelectrophoresis; lidé středního věku; Paraproteinemias; imunoelektroforéza; Multiple Myeloma; Female; Immunoglobulin Light Chains; Aged; senioři; lidé; mnohočetný myelom; ženské pohlaví; isoelektrická fokusace; Male; Middle Aged; paraproteinemie; Isoelectric Focusing; Immunoblotting; mužské pohlaví